An observational feasibility study of a new anaesthesia drug storage tray - Almghairbi, Dalal S.; Sharp, Lisa; Griffiths, Richard; Evley, Rachel; Gupta, Shashi; Moppett, Iain K. (Wiley, 2018)
Drug errors in the anaesthetic domain remains a serious cause of iatrogenic harm. To help reduce this issue, we aimed to explore the potential impact of a simple colour-coded tray to drug preparation and storage on safe drug administration during anaesthesia. Over a six-month period, a total of 30 cases were observed. The observations were conducted at three NHS Trusts by three different trained researchers. Ten observations involved the standard drug trays in ‘normal’ practice and 20 observations, before and after, were conducted where the new “Rainbow trays” were used. A total of 20 semi-structured interviews were conducted immediately upon completing the second observation with the involved anaesthetists. All discussions and detailed notes taken were transcribed and qualitatively analysed using line-byline coding. These codes were then synthesized into themes. Current practice using unicompartmental trays is quick, cheap, and portable but linked to potential or actual harmful errors such as syringe swaps. The Rainbow trays, seem to aid drug identification, allow for drug separation and act as a prompt to guard against drug errors. Limitations to the feasibility of use were around design and placement. The Rainbow trays were perceived as likely to reduce drug errors and improve patient safety. Additionally, there was an overall preference for this novel system at all three sites, as they were perceived to be easy to use and effective.